Pedobarographic, Clinic, and Radiologic Evaluation after Surgically Treated Lisfranc Injury - POLAT, MİNE GÜLDEN; ÖZTÜRK, ORHAN; ÖZEN BERKOL, TUĞÇE; KURU ÇOLAK, TUĞBA (TAYLOR & FRANCIS INC, 2021)
Introduction Lisfranc injuries are rare, often missed, and may cause permanent structural deterioration of tarsometatarsal joint, despite optimal management. Consequently, a Lisfranc injury may lead to disruption of the biomechanics of the normal foot during walking and may alter the plantar pressure distribution, which is essential for proper gait mechanics. Therefore, the main purpose of the study was to specify the dynamic plantar pressure, radiographic and clinical features, after surgically managed Lisfranc injuries. Methods This study was carried out over a period of 10 years and included 62 patients who were surgically treated for Lisfranc injury, with mean 57-month follow-up. Radiological (intermetatarsal, Kite's, first metatarsophalangeal, Meary's, Hibbs' and calcaneal pitch angles, and medial cuneiform-fifth metatarsal distance), pedobarographical, and clinical results with the American Orthopaedic Foot and Ankle Society (AOFAS) midfoot score assessments for both feet were assessed. Results In the radiological assessment, the mean first intermetatarsal (p = 0.006) and Meary's angle (p = 0.000) were decreased on the injured feet compared to the uninjured feet on the anteroposterior and lateral radiographs. In the pedobarographic assessment, the injured feet midfoot contact time increased (p = 0.03), and maximum force (p = 0.001), total peak pressure (p = 0.008), and contact area (p = 0.017) decreased, compared to the uninjured feet. The mean AOFAS score was 75/100 at the final follow-up visit. There was seen to be reduced both contact surface area and time of the midfoot. Conclusion Despite surgical management of Lisfranc injuries, the injured foot does not regain functional, radiological, or pedobarographical levels as compared to the uninjured foot for >= 57 months.
Keywords: Lisfranc; fracture; injury; pedobarography; foot; AOFAS; INTERNAL-FIXATION; OPEN REDUCTION; PRIMARY ARTHRODESIS; JOINT INJURIES; ANKLE; FOOT